The density and spatial distribution of gabaergic neurons, labelled using calcium binding proteins, in the anterior cingulate cortex in major depressive disorder, bipolar disorder, and schizophrenia - Cotter, David; Landau, Sabine; Beasley, Clare; Stevenson, Robert; Chana, Gursharon; MacMillan, Laura; Everall, Ian (Biological psychiatry (1969), 2002)
Background: There is strong evidence for the presence of a deficit in cortical γ aminobutyric acid (GABA) neurotransmission in schizophrenia. In this investigation we have used the calcium binding proteins (CBPs) parvalbumin (PV), calretinin (CR), and calbindin-D28K (CB) as markers of these neuronal populations, and have characterized their pattern and density in schizophrenia, bipolar disorder (BPD), and major depressive disorder (MDD). Methods: We examined the anterior cingulate cortex (ACC) in four groups of 15 brains each from subjects with schizophrenia, MDD, and BPD, and from control subjects. Using immunocytochemistry to identify these distinct neuronal populations, we quantified their areal density and spatial pattern organization. Results: There were reductions in the density of CB-labeled neurons in layer 2 in schizophrenia (34%; p = .04) and BPD (33%; p = .05) compared with control subjects; however, after correction for multiple comparisons these findings no longer attained formal statistical significance. We observed no differences in the density of the neuronal populations labeled by CR or PV in any layer of the cortex in any disorder compared with control subjects. There was increased clustering among PV-labeled neurons in BPD compared with control subjects but no significant differences in the spatial organization of the other neuronal subpopulations in any disorder. Conclusions: The study provides some support for the presence of a deficit in GABAergic neurons in schizophrenia and shows that these changes are not specific to schizophrenia. The findings indicate that there may be a pathophysiological condition, shared by subjects with schizophrenia and BPD, which operates to selectively reduce the number or protein expression of CB-immunoreactive neurons.